Protein foaming-consolidation method for fabrication of high performance porous bioceramics - Sopyan, Iis; -, Suryanto; Fadli, Ahmad; Ramesh, Singh (Trans Tech Publications, Switzerland, 2013)
Abstract. Protein foaming-consolidation method is a facile technique for production of porous materials using egg yolk as pore creating agent. Usage of the yolk in the process offers a number of advantages over other proteins such as egg white and bovine serum albumin (BSA). Various materials were successfully fabricated using this technique. The present paper gives a brief review of the preparation and characterization of the materials through protein foaming-consolidation technique for biomedical application.